Impact of Severe Thermal Injury on Cardiac Contractility and Metabolism - M. A. Goldzon; V. T. Dolgikh (Общая реаниматология)
Objective: to experimentally study cardiac functional and metabolic disturbances in the acute period of severe thermal injury. Material and methods. Experiments were carried out on 25 outbred male albino rats anesthesized with Nembutal (50 mg/kg intraperitoneally). Five-mm-thick copper plates heated up to 60°C were used to simulate thermal injury. Skin contact with the thermal agent lasted 15 seconds. Myocardial contractility and metabolism were examined using the specimen of the isolated isovolumically contracted heart. Results. Severe thermal injury was found to induce acute heart failure caused by cardiac bioenergy impairment, hypoxia, metabolic acidosis, and cardiomyocyte membrane destruction. Key words: thermal injury, cardiac contractility and metabolism.